Concept proposal for IRCF national CPR Registry and update on resuscitation guidelines for infants and children - Lokesh Tiwari; Atul Jindal; Vipul Gupta; L N Taneja; Rakesh Garg; Lokesh R Edara; S S C. Chakra Rao (Wolters Kluwer Medknow Publications, 2022)
There is a lack of scientific data to use as local evidence on resuscitation science from the Indian subcontinent and other developing countries, making it difficult to develop regional guidelines and updates on practice of resuscitation based on the context, resources, infrastructure, geographical variabilities, values, and preferences. In this report, we try to identify key problem statements and plan to expand the list related to resuscitation practices primarily for in-hospital cardiac arrest (CA) in infants and children in India. To stimulate local research and data collection on resuscitation science and practices, Indian Resuscitation Council Federation proposes the concept of National CPR Registry and post-CA care bundle in the form of a checklist targeted for Indian settings.